A ideia é o valor mais importante no design: trabalho criativo no design gráfico - Silva, Glaucia Aparecida da (2014)
Given the changes caused by the so-called flexibilization of the work and production processes, the new analysis on the work category have aimed to understand its current settings and its effects on the daily lives of workers. Dynamism, versatility, engagement, selfmanagement, and creativity are just some of the values preached as ideals to be internalized by the workforce. The analysis of work in graphic design seems to indicate if these values are empirically experienced. We tried to analyze the configuration of the activity, the daily activities of this creative work, the personal and professional networks that determine the entry and stay in the sector, the contradictions between the individual creative potential of these workers against the demands of its customers as well as against the uncertainty and flexibility of this labor market. The work by projects, the intermittency of employment contracts, freelancing and the resulting instability are features that compose this activity despite all the glamor that the designation design brings. Nine semi-structured interviews with graphic designers, both actual and through virtual devices (email, Facebook and Skype), seven of them working in the interior of São Paulo, and two in the state capital were performed.